PENDAMPINGAN INOVASI PRODUK KESET KAKI KAIN PERCA UNTUK MENINGKATKAN STRATEGI PEMASARAN MELALUI E-COMMERCE SHOPEE DI DESA JAJAG - Riza Faishol; Fitriatul Masruroh; Meliantina Meliantina; Khafidzu Rohmah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
The purpose of this activity is to help improve marketing and add new product innovations to the parcain foot doormat, in hopes of achieving increased sales and improving the quality of the selling price of the pared fabric doormat. Some of the problems faced by partners are as follows: 1) lack of innovation in making fabric doormats. 2) Marketing products that still use offline sales and have not used the role of technology. Therefore, through the Real Work Lecture (KKN) program IAI Ibrahimy Genteng Banyuwangi conducted assistance activities to assist in the innovation of parched cloth doormat products and online marketing to increase sales. Mentoring activities are carried out for 4 weeks with 1 meeting per week. The stages of implementation of this assistance include: 1) observation and analysis of problems, 2) activity planning, 3) preparation of schedules of activities and materials, 4) training and mentoring, 5) evaluation stages. The results of the assistance showed that: 1) the mentoring participants have been able to make more innovative fabric doormat products, 2) the mentoring participants have been able to market their products online.